Interdisciplinary Physical Education: A Solution for Fundamental Movement Skills and Numeracy Challenges in Elementary School Students (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
The purpose of this study was to determine the effect of interdisciplinary physical education learning on the fundamental movement and numeracy skills of students. An experimental research method was implemented by integrating interdisciplinary physical education with mathematics. The implementation was carried out for 12 meetings within a period of 6 weeks using a randomized pre-test post-test control group design. The research population was the third-grade students, totaling 4 classes consisted of 135 students. The cluster random sampling technique was used to determine research samples. Class III-B, consisting of 34 students, was selected as Experimental Group 1 (taught by a teacher experienced in interdisciplinary PE). Class III-A, with 33 students, was selected as Experimental Group 2 (taught by a teacher not experienced in interdisciplinary PE) and Class III-C, with 33 students, was selected as the Control Group. The treatment program was implemented for 12 meetings in 6 weeks. The instruments were TGMD-2 and AKM Numeracy test level 2. The results of the study showed a significant increase in the fundamental movement skills of students in Experimental Group 1 of 17.529 (Sig. 0.00) and a significant increase in numeracy abilities of 23.823 (Sig. 0.00). Meanwhile for Experimental Group 2, there was a significant increase in the fundamental movement skills of students of 11.515 (Sig. 0.00) and a significant increase in numeracy abilities of 21.591 (Sig. 0.00). The results of this study concludes that this interdisciplinary physical education program is feasible to be implemented to address the problems in fundamental movement skills and numeracy abilities, particularly in classes taught by experienced teachers.